Vitamin supplementation of sows - Shelton, Nicholas William (Kansas State University, 2014)
A total of 701 pigs were used to evaluate effects of natural vitamin E relative to synthetic vitamin E in sow diets, late gestation feeding level on sow reproductive performance, dietary L-carnitine and chromium on sow reproductive performance, and experimental design on nursery pig trial interpretation. As D-α-tocopheryl acetate increased in the sow’s diet, concentrations of α-tocopherol increased (P < 0.03) in sow plasma, colostrum, milk, pig plasma, and pig heart. Regression analysis indicated that the bioavailability coefficients for D-α-tocopheryl acetate relative to DL-α-tocopheryl acetate ranged from 2.1 to 4.2 for sow and pig plasma α-tocopherol, 2.9 to 3.0 for colostrum α-tocopherol, 1.6 for milk α-tocopherol, 1.8 for heart α-tocopherol, and 2.0 for liver α-tocopherol. Overall, this study indicates that the relative bioavailability for D-α-tocopheryl acetate relative to DL-α-tocopheryl acetate varies depending on the response criteria but is greater than the standard potency value of 1.36. Increasing sow gestation feeding level by 0.9 kg from d 90 of gestation through farrowing reduced (P = 0.001) daily lactation feed intake in gilts, but also resulted in improved conception rate in gilts, whereas increasing late gestation feeding level decreased conception rate in sows (interaction; P = 0.03). Increasing late gestation feed intake in gilts also increased (P < 0.02) pig weaning weights during the second parity. Increasing late gestation feeding levels did not improve performance of older sows. Adding L-carnitine and chromium from chromium picolinate to sow gestation and lactation diets reduced (P = 0.01) the amount of sow weight loss during lactation, however, did not improve (P > 0.05) litter size, pig birth weight, or the variation in pig birth weight. Blocking pens of nursery pigs by BW in a randomized complete block design (RCBD) did not improve the estimates for σ2error compared to a completely randomized design (CRD) where all pens were allotted to have similar means and variations of body weight. Therefore, the added degrees of freedom for the error term in the CRD allowed more power to detect treatment differences for the CRD compared to the RCBD.
Keywords: Sows; Vitamin E; Carnitine; Chromium; Experimental design; Animal Sciences (0475)